2010
DOI: 10.1038/ismej.2010.119
|View full text |Cite
|
Sign up to set email alerts
|

Function-specific response to depletion of microbial diversity

Abstract: Recent meta-analyses suggest that ecosystem functioning increases with biodiversity, but contradictory results have been presented for some microbial functions. Moreover, observations of only one function underestimate the functional role of diversity because of species-specific trade-offs in the ability to carry out different functions. We examined multiple functions in batch cultures of natural freshwater bacterial communities with different richness, achieved by a dilutionto-extinction approach. Community c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
196
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 205 publications
(214 citation statements)
references
References 50 publications
15
196
1
2
Order By: Relevance
“…Both are directly determined by the environmental setting; in addition, functions can be indirectly affected through altered community structure. Experimental tests with assembled bacterial communities at strictly controlled diversity levels have demonstrated that changes in community attributes such as diversity can affect ecosystem processes in various cases (Bell et al, 2009;Langenheder et al, 2010;Peter et al, 2011), one of them quite spectacular (Bell et al, 2005). These results are in line with evidence from a body of similar experiments conducted with higher plants, invertebrates, algae and other microorganisms (Gessner et al, 2010;Cardinale et al, 2011).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Both are directly determined by the environmental setting; in addition, functions can be indirectly affected through altered community structure. Experimental tests with assembled bacterial communities at strictly controlled diversity levels have demonstrated that changes in community attributes such as diversity can affect ecosystem processes in various cases (Bell et al, 2009;Langenheder et al, 2010;Peter et al, 2011), one of them quite spectacular (Bell et al, 2005). These results are in line with evidence from a body of similar experiments conducted with higher plants, invertebrates, algae and other microorganisms (Gessner et al, 2010;Cardinale et al, 2011).…”
Section: Introductionsupporting
confidence: 79%
“…The striking disconnect between bacterial community structure and potential enzyme activities that we observed also appears to be counter to results from controlled experiments with assembled communities, where bacterial diversity (that is, a component of community structure) has been found to matter for ecosystem functioning (Bell et al, 2005;Langenheder et al, 2010;Peter et al, 2011). However, those experiments primarily focused on assessing effects of varying numbers of species or strains rather than the composition of communities and abundance of dominant strains or species as in the present study.…”
Section: Temporal Variability Of Potential Enzyme Activitiescontrasting
confidence: 53%
“…A gradient in microbial biodiversity in an activated sludge community was established using a dilution‐to‐extinction approach (Szabó et al ., 2007; Peter et al ., 2010; Philippot et al ., 2013; Ylla et al ., 2013). In this approach, each dilution theoretically removes the least abundant species from the previous culture, resulting in a less diverse subset of the original community.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, diversity in DSL-MAP soils was not related to degradation, suggesting that diversity may be important in the initial selection of organisms, but less important for actual hydrocarbon degradation. Other recent studies have also shown that the diversity-function relationship depends on the function being considered, and that in some cases, the presence of specific taxa is more important than actual diversity (Salles et al, 2009;Peter et al, 2011). Most of the major taxonomic groups were present in all soils, so it may be that evenness increased the number of groups that could potentially respond to nutrient addition, as the presence of dominant bacterial taxa can sometimes limit the establishment of other bacteria (Heczko et al, 2000).…”
Section: Predictability Of Hydrocarbon Degradation In Arctic Soilsmentioning
confidence: 99%